2013
DOI: 10.1007/978-3-642-32741-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Business Process Models and Domain Knowledge: A Meta-modeling Approach

Abstract: In recent years the problems related to modeling and improving business processes have been of growing interest. Indeed, companies are realizing the undeniable impact of a better understanding and management of business processes (BP) on the effectiveness, consistency, and transparency of their business operations.In this paper we propose to support this modeling effort with an approach that uses domain knowledge to improve the semantic quality of BP models. This approach relies on domain ontologies as a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…One of the studies (Cherfi et al, 2013) that is more relevant to our study in terms of their approach to the problem of managing the relations between the ontology resources and labels in process model collections aligns domain ontologies and business process models to improve semantic quality of business process models. This study proposes four matching rules between process models and domain ontologies.…”
Section: Bpmj 283mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the studies (Cherfi et al, 2013) that is more relevant to our study in terms of their approach to the problem of managing the relations between the ontology resources and labels in process model collections aligns domain ontologies and business process models to improve semantic quality of business process models. This study proposes four matching rules between process models and domain ontologies.…”
Section: Bpmj 283mentioning
confidence: 99%
“…The method addresses the label challenges in business process modeling (Mendling et al, 2014) such as identifying the semantic components of labels, the meaning of terms within labels, homonymous and synonymous terms, and similarity of labels. Previous studies (Cherfi et al, 2013;Fan et al, 2016) have suggested that establishing relationships between ontologies and labels in process model collections even without automation would increase the semantic quality of the process models. We anticipate that using the business process Integrated business process modeling knowledge that resides in process model collections would also improve the quality of ontologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, studies related to process ontologies has addressed the problem using two different approaches. The first approach consists of methods to integrate domain ontologies with process models to build process ontologies (Alkhaldi et al, 2015;Bulegon Gassen et al, 2017;Cherfi et al, 2013;Dimitrov et al, 2007;Fan et al, 2016;Francescomarino et al, 2014;Thomas and Fellmann, 2009). Although these approaches improve efficiency, the formal representation of processes is limited to the knowledge that already exists in domain ontologies.…”
Section: Related Work and Implicationsmentioning
confidence: 99%
“…Therefore, domain ontologies do not necessarily contain information regarding the process entities of the organization. Several methods have been proposed for integrating domain ontologies with process models to build process ontologies (Alkhaldi et al, 2015;Cherfi et al, 2013;Dimitrov et al, 2007;Fan et al, 2016;Francescomarino et al, 2014;Thomas and Fellmann, 2009). While these approaches proved to be useful, they have an inherent limitation; the formal representation of resulting processes is limited to the knowledge that exists in the underlying domain ontologies.…”
Section: Introductionmentioning
confidence: 99%